AN INVESTIGATION INTO SURFACE FINISH IMPROVEMENT OF SMALL PLASTIC PARTS MANUFACTURED THROUGH ADDITIVE MANUFACTURING - NSENGIMANA, JOSEPH (Bloemfontein: Central University of Technology, Free State, 2015)
Nowadays, Additive Manufacturing (AM), also known as 3D printing finds wide application in automotive, aerospace and medical fields. Functional additive manufactured parts must satisfy dimensional accuracy as well as to provide an acceptable quality of surface finish. However the dimensional accuracy of additive manufactured parts are affected by many process variables including accuracy of tessellation from Computer Aided Design (CAD) model, slicing algorithm, data transfer, device motion resolution, powder granulometry, beam offset, process parameters and shrinkage. The surface finish of additive manufactured parts is often poor due to the layer-by-layer manufacturing process of AM. The degree of this so called “stairstepping” is dependent on the type of AM process and layer thickness used. Different post processing techniques can be used to improve the surface finish. Six post processing techniques were investigated in this study to improve the surface finish of small test pieces that were additive manufactured in nylon polyamide, Alumide® and Acrylonitrile Butadiene Styrene (ABS) plastic materials. The techniques include tumbling, shot peening, Computer Numerical Control (CNC) machining, spray painting, undercoat and hand finishing and chemical treatment by dissolving the surface of the test pieces. A Laser Sintering (LS) process was used to manufacture the nylon polyamide and Alumide® test pieces while Fused Deposition Modelling (FDM) was used for the ABS test pieces. A Coordinate Measuring Machine (CMM) also known as Touch probe scan machine was used for assessment of the dimensional accuracy of post processed test pieces compared to the geometry of the “as built” test pieces. The Chisquare test ( 2  ) and the test for differences in deviation range proportions were used to establish the level of significance of differences between ‘“as built” and each post processing technique. It was shown that there exists a significant difference between deviation range proportions as one compares the “as built” to any one of the six considered post processing techniques. For all the three investigated materials, hand finishing technique produced the best improvement of surface finish though this technique was generally characterized by a lack of consistency in distribution of uniform deviation ranges across individual surfaces as well as across entire test pieces. The spray painting improved the surface finish and was found to be consistent in distribution of uniform deviation ranges across individual surfaces as well as across entire test pieces. However this technique led to significant positive deviation ranges from the geometry of the “as built” test piece, thus affecting negatively the dimensional accuracy of the “as built” test piece. On one hand, despite the rounding of the sharp corners and the removal of small protrusions, tumbling and shot peening techniques, without affecting negatively the dimensional accuracy of the test piece, it was found that tumbling and shot peening are the optimal post processing techniques to improve the surface finish of relatively wide surfaces of Laser Sintered nylon and Alumide® test pieces. On the other hand, it was realized that tumbling or shot peening technique should not be applied to ABS test pieces as, in addition to the negative effects of the two techniques on nylon and Alumide® test pieces, tumbling and shot peening damage heavily the surfaces of ABS pieces. Chemical treatment by immersion into acetone bath was found to be the optimal technique for improvement of the surface finish of Fused Deposition Modelled ABS test pieces. Though through CNC machining the surface finish of nylon, Alumide® and ABS test pieces was improved, a relatively high standard deviation in surface finish across the entire test piece was observed. In addition to this, excessive negative deviation ranges were observed on the machined surfaces. This can be attributed to a single error during the calibration of the machine or the setting of the cutting parameters which led to the excessive negative deviation ranges from the geometry of the “as built” test piece. The consideration of individual cutting parameters for each surface inclination angle would reduce the standard deviation and eliminate the risk of excessive negative deviation ranges across the entire test piece. However, this approach would lead to excessive machining time, thus increasing the cost of the process. Finally, it was realized that CNC machining is not an appropriate technique to improve the surface finish of small plastic parts with complex shapes in the form of various inclination angles and small entities such as small conical features, round cavities and protrusions.
Published Thesis